Islamic Corporate Governance, Islamic Social Reporting dan Maqashid Syariah Pada Bank Syariah di Indonesia - Marheni Heni; Liya Emawati (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the effect of Islamic corporate governance, Islamic social reporting and Islamic maqashid on Islamic banks in Indonesia. The variable Islamic corporate governance is proxied by the Board of Directors, Board of Independent Commissioners, Institutional Ownership Audit Committee and Sharia Supervisory Board. The study was conducted on 11 Islamic banks in Indonesia using panel data from 2015-2019 using regression using a random effects model. The results found that only the ICG variables, namely the Independent Board of Commissioners and Institutional Ownership, had an effect on the performance of Islamic maqashid. Meanwhile, other ICG variables and ISR have no effect on sharia maqashid.